Análisis situacional y propuesta de una empacadora de piña para exportación, en agroindustrial “la esperanza”, del cantón Valencia provincia de Los Ríos, año 2011 - Pizarro Loor, Geomaira Elizabeth (2013)
Pineapple demand a broad accounts for 4% to the United States, being the fourth-large stamount of fruit sent to market. In the field work carried out 74% of the employees of Agroindustrial "La Esperanza" believes that the company has a production and sufficient resources to justify the creation of packing as I this quality fruit, approved and certified for export. In addition to significantly increase its revenues, generates jobs and that amounts to enriching social and economic level not only of citizens of Valencia, but also from Ecuador. It is clear that the costs would also increase, however, having an own packing, would improve product quality, avoiding pooling for transportation, saving time and optimizing resources.